Designing Educational Games and Their Benefits - Sharipova nodira (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Educational games are considered interactive activities that should be just as motivating and engaging as regular digital games, but players will learn rather than just be entertained. Despite some limited success over the past few decades, educational games have failed to reach mainstream adoption or success. This chapter claims that such a failure is the result of poor design. Designers can create better educational games once they have a better understanding of how to design games. To this end, three aspects of game design are investigated to see how they relate to the design of successful games. Firstly, how players learn or come to understand something while playing a game. Secondly, how designers can ensure players remain motivated to play the game. Lastly, how both education and motivation should be considered from the perspective of gameplay